Reorganization and management of the pediatric emergency network in Italy and analysis of human and financial resources. - D. Galante (Pediatric Anesthesia and Critical Care Journal (PACCJ))
The pediatric emergency network in Italy plays a vital role in providing critical care for children in urgent need of medical attention. Given the complexity of pediatric emergencies and the need for specialized care, effective organization and management of this network are crucial to ensure the well-being of young patients. This article explores the reorganization and management of the pedi- atric emergency services in Italy, with a focus on human and financial resources. It delves into the challenges and opportunities involved in optimizing these resources, ex- amining current strategies, and providing insights for fu- ture improvements.